DESIGN OF FUZZY EXPERT SYSTEM FOR DETERMINATION OF CULTIVATION EFFECTIVENESS OF ARBUSCULAR MYCORRHIZAL FUNGI AS BIOFERTILIZER - Aziz Kustio, Nur Azizah Azis, Marimin (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT  The use of biofertilizer provides many benefits, including the increase of agricultural production, quality improvement of agricultural products, as well as reduce of the use of artificial fertilizer. One of such biofertilizer is Arbuscular Mycorrhizal Fungi (AMF). In cultivation of AMF, there are some environment factors which influence cultivation effectiveness, such as soil pH, mean temperature, soil water content, and suitability of host plant.  Incompatible factor can give negative impact on AMF cultivation. This research designed an expert system to observe effectiveness value of AMF cultivation based on certain environment factors. This research focused on three AMF species, namely Entrophospora columbiana, Glomus fasciculatum, and Glomus manihotis. This system was built using Fuzzy Inference System (FIS) with four fuzzy parameters: suitability of host plant, soil pH, mean temperature, and soil water content.  Rules as knowledge base had been built with total 144 rules for each AMF species. Mamdani method was used as inference process. The system gave cultivation effectiveness value as output. The effectiveness value showed how effective cultivation process on certain input condition as compared to its best condition. The effectiveness value was also divided into four categories: not effective, slightly effective, moderately effective, and effective. Based on verification result, the system was still unable to gives an accurate effectiveness percentage, although it was quite good on giving right effectiveness category. To be used in real condition, this system must still be developed further. For example, the reasoning system should be added with other factors, such as cultivation time and type of cultivation media.   Keywords: biofertilizer, arbuscular mycorrhizal fungi, fuzzy expert system, Mamdani method